PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KREATIVITAS GURU SD NEGERI SEKECAMATAN KETAHUN - Fadloli Fadloli; Manap Soemantri (Manajer Pendididikan, 2019)
Abstract: this study aims to determine whether there is influence of principal leadership, organizational climate and organizational commitment to the creativity of elementary school teachers in Ketahun of North Bengkulu. The population in this research is all of the elementary school teachers in Ketahun. In this case, there are 166 teachers and the samples are 67 teachers. Data were obtained from questionnaires and analyzed using simple regression and multiple regressions to find out whether there is influence between independent variable to dependent variable. The results showed that the leadership of the principal had a positive and significant effect on the creativity of elementary school teachers in Ketahun is 0.622. Then, the climate of school organization has positive and significant influence to creativity of state elementary school teachers in Ketahun is 0.528. Organizational commitment has a positive and significant impact on the creativity of state elementary school teachers in Ketahun is 0.781. Headmaster leadership, organizational climate and organizational commitment have a greater influence on the creativity of elementary school teachers. There are three independent variables have an influence of 0.824 on the teachers creativity.Keywords: Headmaster Leadership, organizational climate, organizational commitment, and creativity